Answer:
Combine like terms
Step-by-step explanation:
The first step in such equations is to simplify the equation which is done most often by combining like terms, and by combining like terms i mean for example:
1 + 5 + 3x = 4y + z
You will combine the like terms (those that can be added or subtracted):
6 + 3x = 4y + z
In our example, combining terms would be adding 2x/3 and 1x/3 to give
3x/3 + 2 = 5
The equation is now simple and easy to solve as you simplify 3x/3 to 1x and then proceed to rearrange the equation to yield the value of x
Hope this helps!
The answer is C. -4n⁴+3n.
Separate the expression by its like terms.
12n-2n⁴-10n-2n⁴+n
12n+(-10n)+n=3n
-2n⁴+-2n⁴=-4n⁴
The simplified expression comes out to -4n⁴+3n.
I hope this helps you
12=3.4=3.2^2